Golden wings and other stories about birders and birding - Dunne, Pete, 1951- (Corrie Herring Hooks series, 2003)
Annotation Dubbed the "Bard of America' Bird-Watchers" by the Wall Street Journal, Pete Dunne knows birders and birding--instinctively and completely. He understands the compulsion that drives other birders to go out at first light, whatever the weather, for a chance to maybe, just maybe, glimpse that rare migrant that someone might have spotted in a patch of woods the day before yesterday. And yet, he also knows how ... well ... strange the birding obsession becomes when viewed through the eyes of a nonbirder. His dual perspective--totally engrossed in birding, yet still aware of the "odd birdness" of some birders--makes reading his essays a pure pleasure whether you pursue "the feather quest" or not. This book collects forty-one of Dunne' recent essays, drawn from his columns in Living Bird, Wild Bird News, the New Jersey Sunday section of the New York Times, Birder' World, and other publications. Written with his signature wit and insight, they cover everything from a moment of awed communion with a Wandering Albatross ("the most beautiful thing I'd ever seen") to Dunne' imagined "perfect bird" ("The Perfect Bird is the size of a turkey, has the wingspan of an eagle, the legs of a crane, the feet of a moorhen, and the talons of a great horned owl. It eats kudzu, surplus zucchini, feral cats, and has been known to predate upon homeowners who fire up their lawn mowers before 7:00 A.M. on the weekend."). The title essay pays whimsical, yet heartfelt tribute to Dunne' mentor, the late birding legend Roger Tory Peterson